Perempuan Lembak Dalam Pergulatan Tradisi Keagamaan - Rodiyah Rodiyah (Institut Agama Islam Negeri Bengkulu, 2019)
The various traditions that have implications for women's lives, including the traditions that exist in Indonesia in each region. Lembak community is one part of a tribe in Bengkulu Province, which has a unique tradition as a local power. In examining this problem, the author uses a qualitative method using the phenomenological thinking section. The author analyzes the data found in the field using bidaya hemeneutik, Cliford Great, according to the researchers photographing the Lembak community in accordance with the perceptions of the culture owner community that is the Lembak community and also the views of the community outside the culture.